Masks of Chronic Prostatitis: Overactive bladder and Myofascial Syndrome. Case study - E. V. Kulchavenya; A. A. Baranchukova (Вестник урологии, 2019)
Prostatitis is a chronic disease that does not respond well to therapy. It is prone to frequent relapses and does not have a clear and unambiguous clinical picture, which can lead to diagnostic failure. A case of overactive bladder and myofascial syndrome described. The clinical picture was interpreted as «chronic prostatitis» erroneously. Differentiated analysis of the International Prostate Symptom Score (IPSS) and NIH-CPSI (National Institute of Health Chronic Prostatitis Symptom Index) questionnaires, as well as palpation of trigger points made it possible to establish the correct diagnosis. The following drugs were prescribed: Trospium chloride (Spasmex® ) 15 mg twice a day, Baclоfen (Baclophenum) 10 mg daily, Combilipen (B vitamins multicomplex) intramuscularly, Nimesulide (Nimesulide) orally, and locally low-intensity laser therapy. The patient noted a marked improvement after 14 days: the pain intensity decreased from 8 points to 1, urination urgency was not noted, nocturia stopped. The quality of life (QoL) accordingly improved to 1 point on the IPSS scale. The total score for domains III and IV decreased from 11 to 3 according to the NIH-CPSI symptom scale of chronic prostatitis. The pronounced positive dynamics of the patient’s state of health has confirmed the accuracy of the diagnosis and treatment.